Microstructure and Compositional Defects Affects Proton Conductivity and Reactions in Y-doped BaZrO3 Thin Films. (26th April 2016) - Yang, Nan; Di Bartolomeo, Elisabetta; Foglietti, Vittorio; Cantoni, Claudia; Belianinov, Alex; Tebano, Antonello; Licoccia, Silvia; Lee, Tien-Lin; Schlueter, Christoph; Kalinin, Sergei V.; Balestrino, Giuseppe; Aruta, Carmela
Abstract : In this paper, we report on BaZr0.8 Y0.2 O3-x (BZY) thin films grown on highly mismatched NdGaO3 (110) substrates by RHEED assisted pulsed laser deposition. The conduction and electrochemical performances are studied by Electrochemical Impedance Spectroscopy and Electrochemical Strain Microscopy respectively. Conductivity, as well as electrochemical response improves while decreasing the thickness, indicating that the proton movement is prompt at the defective interface region. Structural defects at the interface between film and substrate are clearly displayed by x-ray diffraction, RHEED patterns and transmission electron microscopy. The role of chemical defects on BZY film properties is elucidated by Hard X-ray Photoelectron Spectroscopy. Our results demonstrate that both structural dislocations and chemical defects influence the proton conduction and reaction process in BZY thin films.